Using net-zero carbon debt to track climate overshoot responsibility - Setu Pelz; Gaurav Ganti; Robin Lamboll; Luke Grant; Chris Smith; Shonali Pachauri; Joeri Rogelj; Keywan Riahi; Wim Thiery; Matthew J. Gidden (Proceedings of the National Academy of Sciences, 2025)
Current emissions trends will likely deplete a 1.5 °C consistent carbon budget around the year 2030, resulting in at least a temporary exceedance, or overshoot. To clarify responsibilities for this budget exceedance, we consider “net-zero carbon debt,” a forward-looking measure of the extent to which a party is expected to breach its “fair share” of the remaining budget by the time it achieves net-zero carbon emissions. We apply this measure to all vetted mitigation scenarios assessed in the Intergovernmental Panel on Climate Change’s Sixth Assessment Report and two scenarios that model current policies and pledges, using an illustrative equal per capita allocation of a remaining 1.5 °C carbon budget starting in 1990. The resulting regional carbon debt estimates inform i) the scale and pace of regional carbon drawdown obligations necessary to address budget exceedance and ii) relative regional responsibilities for increased lifetime exposure to extreme heatwaves across age cohorts due to budget exceedance. Our work strengthens intergenerational equity considerations within an international climate equity discourse and informs the implementation of effort-sharing mechanisms that persist beyond the exhaustion of a rapidly dwindling remaining carbon budget.